Cytokine profile in patients with chronic non-bacterial osteomyelitis, juvenile idiopathic arthritis, and insulin-dependent diabetes mellitus. (July 2021) - Kostik, Mikhail M.; Makhova, Maria A.; Maletin, Alexei S.; Magomedova, Shamai M.; Sorokina, Lybov S.; Tsukasaki, Masayuki; Okamoto, Kazuo; Takayanagi, Hiroshi; Vasiliev, Dmitriy S.; Kozlova, Darya I.; Mushkin, Alexander Yu.
Highlights: Patients with CNO had increased level of pro-inflammatory cytokines. Monocyte-driven inflammation takes the crucial role in the pathogenesis of CNO. Cytokines may prove valuable as biomarkers and potential therapeutic targets for CNO. Abstract: Objectives: Our study aimed to evaluate the cytokine levels in pediatric chronic non-bacterial osteomyelitis (CNO) patients and compare these with other immune-mediated diseases and healthy controls. Methods: In this prospective study, we included 42 children with CNO, 28 patients with non-systemic juvenile idiopathic arthritis (JIA), 17 children with insulin-dependent diabetes mellitus (IDDM), and 30 healthy age-matched controls. In each of the CNO patients and comparison groups, the levels of 14-3-3-η protein, S100A8/A9 protein, interleukin-4 (IL-4), interleukin-17 (IL-17), interleukin-18 (IL-18), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α) were measured by ELISA assay. Results: All studied cytokines in the CNO patients were significantly higher than controls, and IDDM, 14-3-3-η protein, IL-18, IL-4, IL-17, IL-1β, and TNF-α were less than in JIA patients. In the discriminant analysis, ESR, 14-3-3 protein, S100A8/A9, IL-18, IL-4, and TNF-α can discriminate CNO from JIA, and 14-3-3 protein, S100A8/A9, IL-18, IL-17, IL-4, and TNF-α can distinguish CNO from other diseases and HC. Conclusion: The increased level of pro-inflammatory cytokines confirms the role of monocyte-driven inflammation in CNO patients. Cytokines may prove valuable as biomarkers and potential therapeutic targets for CNO.